A Study to Analyze Perception of Customers towards Visual Merchandising Techniques in Indore City - Singh, Mallika; Shrivastava, Deepak (Journal of Commerce and Trade, 2016)
Visual merchandising techniques are the important factor which influence the customers shopping pattern and also gives chance to retailers to beautify their stores. With the help of VM techniques retailers can make their stores appealing and can create an attractive image of stores in the mind of customers. The present study attempts to analyze the perception of customers in the direction of visual merchandising. For the purpose store ambiance, design layout and window display techniques of VM were considered to study the perception of customers. The t-independent test was applied and results reported that the perception of males and females on all the three techniques have different. In other words, male customers and female customers perceive these techniques differently.